Drug dealing and drug using behaviors among people who inject drugs in Colombia: A cross-sectional study. (2nd November 2017) - Toro-Tobón, David; Berbesi-Fernandez, Dedsy; Mateu-Gelabert, Pedro; Segura-Cardona, Ángela M.; Montoya-Vélez, Liliana P.
ABSTRACT: Introduction: People who inject drugs (PWID) are highly exposed to drug-dealing networks. In Colombia, a recent dramatic increase in drug consumption has been reported. However, involvement of PWID in drug dealing, their demographics, and drug using behaviors has not been studied. Methods: A cross-sectional study involving 1, 099 PWID recruited by Respondent Driven-Sampling in five Colombian cities was conducted in 2014. Correlates of demographic characteristics, drug dealing, and injection behaviors were examined by multivariate analysis, and a binary logistic regression model. Results: Drug-dealing PWID were predominantly male (86%) with a mean age of 26 years. 56% of participants—of whom 64% had low familial socioeconomic status—had been involved in drug dealing in the previous six months. Compared to non-drug-dealing PWID, drug-dealing PWID reported higher daily injection rate (AOR: 1.3), higher odds of injection equipment confiscation by the police (AOR: 1.4), and were less likely to pay for the drugs they injected (AOR: 0.6). Conclusions: Involvement of Colombian PWID in drug dealing was higher than previously reported, and drug-dealing PWID presented sociodemographic vulnerabilities and risky injection practices. Addressing these findings may lead to effective policy design and implementation, decreased drug-dealing involvement, harm reduction, and consumption prevention.